(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
The genus Senecio L. is one of the largest genera of flowering plants and is an important member of the tribe Senecioneae (Asteraceae). Phenotypic information, including a broad range of morphological characters is very crucial for phylogenetic reconsideration of any family, tribe or genus. In the family Asteraceae, very little attention has been paid to cypselar diversity, though it is regarded as taxonomically valuable. A sincere attempt has been made to study detailed cypselas macro and micro-morphological features of four species of Senecio L. These diacritical features could be used to strengthen current inter-specific concept of Senecio L. DOI: http://dx.doi.org/10.3329/bjpt.v21i1.19251 Bangladesh J. Plant Taxon. 21(1): 13-17, 2014 (June)